Producción científica de la Sociedad Argentina de Genética en los últimos años; los indicadores de sus congresos - Baringoltz, E. (2010)
National scientific systems often require the use of techniques provided by Bibliometrics in order to measure the production in science and technology. A set of indicators built for that purpose make easier the mathematical and statistical analysis of bibliographic data included in science-and-tech publications. Free communications and lectures presented to congresses and scientific meetings may be one of the raw materials for them. SAG has annually organized in Argentina the national meeting of Genetics for more than 40 years, but for the present analysis, only data found in books of abstracts from 1984 to 2009 have been reviewed. The number of full conferences, symposia, and communications in posters were recorded and tabulated. We also provide here a classification of invited lecturers according to country of origin, and of the free communications according to sessions where they were presented, comparing the production among quinquennial periods. Sustained production along this period of time – and even important growing of several sections of the congress – are some of the results observed after the analysis. We also find remarkable the allocation of some room for the discussions on teaching in this type of meeting, because they are the very first contact of young students with their future profession. We conclude that SAG honors its commitment to promote the generation and spreading of scientific knowledge through its Genetic Congresses, the continuity and growth of which clearly indicating that there is a need for their existence.